Combination Tea of Vernonia Amygdalina Del. Leaves and Syzygium Polyanthum Leaves as Complementary Therapy for Type 2 Diabetes Mellitus - Wahyudi, Wahyudi; Sinaga, Haryanti; Tanjung, Hazira Yulistia (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Type 2 diabetes mellitus (T2DM) is a global health problem that increase every year. This study aims to test the effectiveness of a combination of African leaf and bay leaf tea as a complementary therapy for type 2 diabetes mellitus (TEDAS). This experimental research used mice induced with alloxan. Treatment and observation of antidiabetic effects were carried out for 12 days of treatment and KGD was measured every 3 days. There were 6 test groups including positive control using glibenclamide, negative control, no treatment, TEDAS1, TEDAS2 and TEDAS3. Phytochemical screening shows that TEDAS contains secondary metabolite compounds including tannins, alkaloids, flavonoids and saponins. The results showed that all TEDAS groups significantly reduced blood glucose levels. KGD examination on day 12 showed that the KGD in the group without treatment was 87, negative control 126 mg/dL, positive control 90 mg/dL, TEDASI 95 mg/dL, TEDAS2 91 mg/dL, and TEDAS3 96 mg/dL. The most effective group is TEDAS2 with glibenclamide + DA 100mg/Kgbb + DS 50mg/Kgbb treatment. Research indicates that TEDAS is effective as a complementary therapy for T2DM.